(untitled) (New Jersey, 1962)
Contents: Alphabetical index; Drug, chemical and pharmacological index; Therapeutic indications index; Product identification section; Pofessional products information; Manufacturers' service material.
Keywords: Dược liệu,Thuốc,Materia medica,Materia medica,Materia medica,Materia medica; Từ điển,Từ điển,Dictionaries,Dictionaries,Dictionaries,Dictionaries